Analisis Kesiapan Madrasah Salafiyah Wustha Pondok Pesantren Raudhatul Qur’an 1 Klaten dalam Insersi Kurikulum Cinta - Shidiq Agung Sutrisno (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
This study aims to analyze the implementation of the Love Curriculum at Madrasah Salafiyah Wustha Pondok Pesantren Raudhatul Qur'an 1 Klaten, focusing on identifying obstacles, potential, and support needed to optimize its application in shaping student character. This study uses a descriptive qualitative approach. Data collection techniques were carried out through triangulation, which included interviews, observations, documentation studies, and the distribution of questionnaires to teachers at Madrasah Salafiyah Wustha Pondok Pesantren Raudhatul Qur'an 1 Klaten. The collected data was then analyzed thematically to answer the research questions. The results showed that the Love Curriculum had been implemented well and had a positive impact on character building. However, several significant obstacles were identified, such as selfish attitudes among some students, time constraints, and inadequate learning facilities. On the other hand, strong support from the madrasah principal and parental involvement were identified as significant potentials that could be developed. The ustadz training program has also proven to play an important role in improving the quality of value-based teaching. The implication of this study is the need to develop more varied and comprehensive strategies to overcome existing obstacles. The limitation of this study lies in its scope, which is only on one madrasah, so the findings may not be widely generalized without further study. This study makes an original contribution by exploring in depth the implementation of the Love Curriculum, an innovative model in character education at the madrasah ibtidaiyah level. The value of this study lies in the practical recommendations it provides for strengthening the synergy between madrasahs, ustadz, and parents in order to maximize character education.